2014
DOI: 10.1016/j.apcbee.2014.10.059
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Landscape Design on House Prices and Values in Residential Development in Urban Areas

Abstract: Focusing on a world class living environment, a good quality residential area can be highlighted as an important issue in creating a sustainable living environment. However, limited green spaces within the proximity of residential properties are not supporting the landscape space and are not conducive to living space. The aim of the paper is to investigate the impact of landscape design on house prices and values in residential development particularly in urban areas. The paper employed quantitative approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…The other previous researches have also shown that elements of landscape design consists of fountain, gazebo, vegetation, bench, pergola, railing, and park can influence house value in Malaysia, because it gives a comfortable and safety feeling (Hussain et al, 2014). In line with the previous research, this study focuses on landscape elements in Surabaya by adding some elements such as shape and color of the vegetation, and road equipment.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The other previous researches have also shown that elements of landscape design consists of fountain, gazebo, vegetation, bench, pergola, railing, and park can influence house value in Malaysia, because it gives a comfortable and safety feeling (Hussain et al, 2014). In line with the previous research, this study focuses on landscape elements in Surabaya by adding some elements such as shape and color of the vegetation, and road equipment.…”
Section: Introductionmentioning
confidence: 59%
“…Landscape design is one of the most important elements in residential design because it can make genius loci that give safety feeling and comfort (Hussain et al, 2014). In other words, residential landscape does not only provide view, but also the benefits of relaxation for housing residents, accordingly the combination of shape and function of residential landscape are the most important thing.…”
Section: Landscape Elements and Perceptionmentioning
confidence: 99%
“…Through a questionnaire survey and observations, researchers investigated the impact of landscape design on home prices in urban areas. They concluded that the perception of quality and quality in landscape design would be applied to residential development (Hussain et al, 2014). The size, position and environmental features of the selected land-plot can influence the thermal comfort of the future house and the energy savings due to sun exposure in the world (Almumar, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here, the researcher has compiled several previous research conducted earlier that can help determine the characteristics quality be implemented afterwards. Khoiry, Tawil, Hamzah, Ani, & Sood, (2012), Ramzi, Hussain, Tukiman, & Zen, (2014) and Zahirovichherbert & Gibler, (2014) have provided valuable insights towards characteristics qualities and the researcher has summed up that there were eight main characteristics that determine and affects the house prices. The characteristics were functionality, presentation, environment, amenities, community, management, location and access.…”
Section: Determination Factor Of Characteristics Qualities Of Houses With Pricesmentioning
confidence: 99%